Stretching and Kibble scaling regimes for Hubble-damped defect networks - Martins, C.J.A.P.; Rybak, I. Yu.; Avgoustidis, A.; Shellard, E.P.S. (American Physical Society, 2016)
The cosmological evolution of topological defect networks can broadly be divided into two stages. At early times they are friction dominated due to particle scattering and therefore nonrelativistic and may either be conformally stretched or evolve in the Kibble regime. At late times they are relativistic and evolve in the well-known linear scaling regime. In this work we show that a sufficiently large Hubble damping (that is a sufficiently fast expansion rate) leads to a linear scaling regime where the network is nonrelativistic. This is therefore another realization of a Kibble scaling regime and also has a conformal stretching regime counterpart which we characterize for the first time. We describe these regimes using analytic arguments in the context of the velocity-dependent one-scale model, and we confirm them using high-resolution 4096[superscript]3 field-theory simulations of domain wall networks. We also use these simulations to improve the calibration of this analytic model for the case of domain walls.